APPENDIX C: CONSTRUCTING A TABLE - Vacha, Edward (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Tables clarify what you have to say about the data. However, a table must be carefully constructed with clear labels and headings if the reader is to understand it. Notice in the following example the use of headings and subheadings to label the data and categories.